A revocable certificateless encryption scheme with high performance. (2018) - Yinxia, Sun; Zhuoran, Zhang; Limin, Shen
Featuring no key escrow and no certificate, certificateless public key cryptography (CLPKC) has received much attention. A necessary problem in CLPKC is how to revoke a compromised/misbehaving user, which still remains to be efficiently solved: all existing methods are not practical for use owing to either enormous computation (secret channels), or a costly mediator. In this paper, we present a new approach for revocation in CLPKC and give a revocable certificateless encryption (RCLE) scheme. In the new scheme, a user's private key contains three parts: an initial partial private key, a time key and a secret value. The time key is updated at every time period and is transmitted over a public channel. Our construction offers higher performance than previous solutions. Based on the bilinear Diffie-Hellman problem, our RCLE scheme is provably secure in the random oracle model.